Medical industry at tumor board: Three‐years analysis of the open payments database and comparison of oncologic specialties. Issue 4 (22nd November 2017) - Baadh, Amanjit S.; Patel, Mikin; Patel, Ketan; Ahmed, Osman
Abstract : Background and Objectives: To analyze and contrast medical industry payments across U.S. oncologic providers, including hematology‐oncology (HO), surgical oncology (SO), interventional radiology (IR), and radiation oncology (RO). Methods: Open‐payment‐data for each provider including provider specialty, state of practice, industry payor, reason for payment, and amount was compiled for each transaction between 2013 and 2015. Total, mean, and median payment amounts per‐provider were calculated for each specialty. Tukey's‐method was used to identify and remove statistical outliers and Kruskal‐Wallis‐test with Bonferonni‐post‐hoc‐analysis was used to evaluate for differences in total payments received per‐provider across specialties. The percentage of providers accepting payments within each specialty were compared by Marascuilo's multiple‐proportion‐comparison. Results: Total aggregate payment amount (and number of transactions) for HO, SO, IR, and RO was 164 743 746 (778 007), 7 925 467 (15 031), 49 817 380 (44 939), and 13 643 739 (49 778), respectively. Corrected‐median (and corrected‐mean) payments‐per‐specialty were 676 (1796), 330 (1209), 487 (1301), and 242 (766). A significantly higher proportion of HO providers accepted payments than both RO (97% vs 80%, P < 0.0001) and IR (97% vs 78%, P < 0.0001). The mean total payment received per‐provider differed significantly across specialties ( P = 0.0001). HO providers, on average, received significantly more payment‐per‐provider during the study period ( P < 0.001) compared to all others while RO and IR received significantly less ( P < 0.0001). Conclusions: Among industry payments made to oncologic providers, HO received the highest median and corrected‐mean amounts along with the highest proportion of providers receiving open payments.